2021
DOI: 10.1016/j.apmr.2021.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pulmonary Rehabilitation in Interstitial Lung Disease, Including Coronavirus Diseases: A Systematic Review and Meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 61 publications
2
33
1
5
Order By: Relevance
“…About 14% of COVID-19 patients experience severe disease, and 6% develop critical illness. According to the most recent clinical guidelines, pulmonary rehabilitation could improve physical and psychological conditions, including exercise training, education, and behavioral changes [61]. Patients who underwent respiratory illness and mixed respiratory and surgical populations could improve muscle strength, walking, and functional ability with significant positive effects in the six minutes walking test (6MWT) and Barthel index [62].…”
Section: Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…About 14% of COVID-19 patients experience severe disease, and 6% develop critical illness. According to the most recent clinical guidelines, pulmonary rehabilitation could improve physical and psychological conditions, including exercise training, education, and behavioral changes [61]. Patients who underwent respiratory illness and mixed respiratory and surgical populations could improve muscle strength, walking, and functional ability with significant positive effects in the six minutes walking test (6MWT) and Barthel index [62].…”
Section: Rehabilitationmentioning
confidence: 99%
“…Patients who underwent respiratory illness and mixed respiratory and surgical populations could improve muscle strength, walking, and functional ability with significant positive effects in the six minutes walking test (6MWT) and Barthel index [62]. Pulmonary rehabilitation has been applied with positive results in severe cases with pulmonary fibrosis [61].…”
Section: Rehabilitationmentioning
confidence: 99%
“…In addition, pulmonary rehabilitation is also necessary for COVID-19 patients. It was demonstrated that different pulmonary rehabilitation interventions, including combined exercise (aerobic with strength), combined exercise with specific respiratory exercises, and aerobic exercises with specific respiratory muscle training, could obviously improve pulmonary functional and quality of life of patients recovered from severe COVID-19 ( 78 ). It was also recommended that rehabilitation care is crucial for patients with severe COVID-19, which should be implemented as soon as possible, and performed at the same time with regular treatment of COVID-19 according to the correct assessment ( 79 ).…”
Section: Skeletal Complicationmentioning
confidence: 99%
“…We accept, however, that differences in pathophysiology, comorbidities, phenotypes/endotypes, and therapeutic options between diseases means disease-specific evidence is essential to inform clinical decision-making. In this issue of CHEST, Nolan and colleagues 3 contribute knowledge to the increasing body of evidence of PR for idiopathic pulmonary fibrosis (IPF) 4,5 and present interesting food for thought for guideline developers and policymakers.…”
mentioning
confidence: 99%